2020
DOI: 10.3389/fnagi.2020.580772
|View full text |Cite
|
Sign up to set email alerts
|

GLT-1 Knockdown Inhibits Ceftriaxone-Mediated Improvements on Cognitive Deficits, and GLT-1 and xCT Expression and Activity in APP/PS1 AD Mice

Abstract: Objective Glutamate transporter-1 (GLT-1) and system x c – mediate glutamate uptake and release, respectively. Ceftriaxone has been reported to upregulate GLT-1 expression and improve cognitive decline in APP/PS1 mice. The aim of the present study was to elucidate the role of GLT-1 in ceftriaxone-mediated improvement on cognitive deficits and associated changes in xCT (catalytic subunit of system x c – ) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…Abnormal activation of extrasynaptic NMDAR is one of the mechanisms involved in the occurrence and development of synaptic plasticity damage and cognitive impairment in AD (Bordji et al, 2010; Sun et al, 2016; Talantova et al, 2013; Wang & Reddy, 2017). Our recent study has shown that Cef plays an anti‐AD role by upregulating the GLT‐1 expression, promoting glutamate–glutamine cycle, and improving cognitive impairment in APP/PS1 AD mice (Fan et al, 2018; Gao et al, 2020). This study demonstrated that Cef improved cognitive impairment and synaptic plasticity in APP/PS1 AD mice by inhibiting extrasynaptic NMDAR and increasing STEP 61 expression, and provided new evidence for elucidating the mechanism by which Cef plays an anti‐AD role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abnormal activation of extrasynaptic NMDAR is one of the mechanisms involved in the occurrence and development of synaptic plasticity damage and cognitive impairment in AD (Bordji et al, 2010; Sun et al, 2016; Talantova et al, 2013; Wang & Reddy, 2017). Our recent study has shown that Cef plays an anti‐AD role by upregulating the GLT‐1 expression, promoting glutamate–glutamine cycle, and improving cognitive impairment in APP/PS1 AD mice (Fan et al, 2018; Gao et al, 2020). This study demonstrated that Cef improved cognitive impairment and synaptic plasticity in APP/PS1 AD mice by inhibiting extrasynaptic NMDAR and increasing STEP 61 expression, and provided new evidence for elucidating the mechanism by which Cef plays an anti‐AD role.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, Cef was administered to the mice via an intraperitoneal injection once daily for 14 days at a dose of 200 mg/kg in all groups subjected to the Cef treatment. This Cef dose and protocol significantly upregulated the GLT‐1 expression and its glutamate uptake (Gao et al, 2020; Rothstein et al, 2005). The mice in the wild‐type and APP/PS1 groups received normal saline as vehicle control of Cef with the same protocols.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After blocking, slides were incubated in primary antibody (guinea pig anti-GLT-1, 1:500, Abcam, AB1783) overnight at 4 ℃. The specificity of this particular antibody is nicely demonstrated in a recent study using Western blot and immunohistochemistry showing clear GLT-1 reductions in GLT-1 ± mice and significant GLT-1 upregulation following ceftriaxone treatment [ 33 ]. Slides were then washed three times in 0.01 M PBS for 10 min each and incubated in secondary antibody (Alexa fluor 647-conjugated donkey anti-guinea pig, 1:500, Jackson Immunoresearch Labs) at room temperature for 2 h. After the final washes in 3 times in 0.01 M PBS for 10 min each, slides were cover slipped using Dako mounting medium containing DAPI.…”
Section: Methodsmentioning
confidence: 99%